Attitudes and practices of community pharmacists and barriers to their participation in public health activities in Yemen: mind the gap - Seena A. Yousuf; Mohammed Alshakka; Wafa F. S. Badulla; Heyam Saad Ali; P. Ravi Shankar; Mohamed Izham Mohamed Ibrahim (BMC, 2019)
Abstract Background Patients in Yemen commonly visit community pharmacies to obtain consultation or treatment for common ailments. Community pharmacists have an opportunity to optimize medication use and improve patient outcomes. This study aimed to evaluate the attitudes and practices of community pharmacists regarding their participation in public health activities and barriers to their participation in these activities. Methods This cross-sectional study was carried out among community pharmacists working in pharmacies located in urban areas of the Aden governorate of Yemen from March to June 2017 using a self-administered questionnaire. We selected pharmacies from a line list using proportional sampling according to the number of pharmacies in the urban areas of each district. The questionnaire contained four sections: demographic characteristics, attitudes, practices, and barriers encountered. Data were analyzed descriptively, and the Chi-square test was used for analyzing the association of variables (alpha = 0.05). Results The questionnaire was distributed to 200 community pharmacists working in community pharmacies. Of the 200 respondents, 62% (n = 124) were male. Overall, the mean age (sd) was 30.0 years (8.6) with the number of years of work experience between 2 and 9.9 years (n = 158, 79%). On average, 62.3% of the pharmacists had a positive attitude toward participation in public health activities. Providing education to stop tobacco chewing, smoking, alcohol drinking and improve oral hygiene was an important activity of the community pharmacists. Blood pressure measurements (86%, n = 172) and glucose tests (45%, n = 90) were commonly conducted for clients. Lack of time (71%, n = 142) and lack of teamwork (70%, n = 140) were mentioned as common barriers to participation in public health activities. Conclusions Community pharmacists had a positive attitude toward public health activities. Health education and routine health tests were important practices of the community pharmacists. Barriers need to be overcome to enable more active participation by community pharmacists in public health activities by consulting with all stakeholders, assessing the situation, considering alternatives and taking action.